Hubungan antara Kontrol Sosial Masyarakat dengan Perilaku Sosial Anak Usia Dini - Mila Anggraini; Solfema Solfema; Ismaniar Ismaniar (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2018)
The development of early childhood in social behavior in RT 03 RW 06, Sapih Sungai Kelurahan, Kota Padang, in low low category. This is allegedly due to the low social control in the community. This study aims to reveal the picture of social control of society, the image of social behavior of early childhood, and the relationship between the two variables. This research is correlational type research. The population of this study was 68 people and 60% were sampled, with stratified random sample technique. Data collection tools used questionnaires and analysis techniques using the formula percentage and product moment. The results of the study included: (1) community social control in the low category, (2) early child social behavior in low category, (3) there was a significant correlation between social control of society and social behavior of early child. Suggestions in this study other than to the parents, the community needs to improve social control of the community so that children have social behavior that can be accepted well in the community.